The Tabot Tradition: Exploring the Spread of Islam and Cultural Interaction in Bengkulu - Sativa, Annisa; Irham, M. Iqbal; Wanto, Sugeng (Jurnal Sosiologi USK (Media Pemikiran & Aplikasi), 2023)
The Tabot tradition is an important part of the Bengkulu cultural and religious heritage, which shows a close interaction between traditional customs and Islamic beliefs. The study aims to describe the Tabot tradition in Bengkulu and its relationship with the process of Islams entry into the country using a literature study approach. This study showed The process of Islamization in Bengkulu involved the economic activities of Muslim traders, intermarriage, Sufi teachings, and the development of the arts. Islam reached Bengkulu in the 15th or 16th century, primarily through contacts with Minangkabau and Palembang. The introduction of Islam to Bengkulu resulted in the formation of small kingdoms and the establishment of Islamic burial sites and manuscripts. The Tabot tradition, an annual ceremony commemorating the death of Imam Husayn, was brought to Bengkulu by Indian Bengalis and later blended with local traditions. This tradition demonstrates the close interaction between traditional customs and the Islamic faith in Bengkulu.